Investigação de preditores cardiorrespiratórios em pacientes internados e sobreviventes de COVID-19 acompanhados por 6 meses após alta hospitalar - Boteon, Thais Batistella (Universidade Federal de São Carlos, 2025)
Introduction: COVID-19 is a multisystem disease in which patients with a higher number of comorbidities tend to experience more severe progression, with viral pneumonia appearing to be the most severe respiratory manifestation. Patients may continue to experience symptoms for months after the resolution of the acute phase of COVID-19, with wide variability in intensity, affected systems, and duration. It is believed that patients with greater pulmonary involvement during hospitalization may present with unfavorable cardiorespiratory outcomes in the post-discharge follow-up, associated with greater functional impairment. Objectives: I) To identify clinical, laboratory, and radiological predictors during COVID-19 hospitalization; II) To monitor unfavorable respiratory outcomes at 1, 3, and 6 months after hospital discharge. Methods: This was a prospective, observational, and longitudinal clinical study involving unvaccinated patients diagnosed with and hospitalized for COVID-19. During hospitalization, patients were assessed for comorbidities, cardiovascular risk factors, symptoms, as well as laboratory and imaging tests. Patients who were discharged were followed up at 1, 3, and 6 months and underwent clinical evaluation and the following complementary tests: laboratory tests, transthoracic echocardiography, chest computed tomography, spirometry, six-minute walk test (6MWT), and quality of life (SF-36) and dyspnea (mMRC) questionnaires. Results: A total of 44 patients were evaluated; 45.5% were admitted to the ICU, and 22.7% required invasive mechanical ventilation (IMV). A total of 90.9% of patients required supplemental oxygen, and 61.4% underwent non-invasive mechanical ventilation (NIV). Hospitalization data analysis showed a correlation between lower lymphocyte counts and the need for IMV (p = 0.011). ROC curve analysis identified a lymphocyte count ≤ 971 cells/mm³ (p = 0.01) with 80.0% sensitivity and 61.0% specificity for predicting the need for IMV, with complete lymphocyte recovery observed within one month after hospital discharge. Regarding the six-month follow-up, there was improvement in chest CT findings, global longitudinal strain (p = 0.045), exercise tolerance on the 6MWT (post-test Borg dyspnea scale, p = 0.007), quality of life (physical role limitations on the SF-36, p = 0.02), and spirometry results with statistically significant improvements in forced vital capacity (p = 0.005), forced expiratory volume in the first second (p = 0.021), and slow vital capacity (p = 0.002), as well as in their respective predicted percentage values (p = 0.011, p = 0.015, and p = 0.001, respectively). The results also demonstrated that an mMRC score > 2 showed good sensitivity and specificity for identifying an average SF-36 score < 70 at one and three months post-discharge (AUC = 0.85 [95% CI: 0.72–0.97; p < 0.001] and AUC = 0.91 [95% CI: 0.80–1.00; p = 0.001], respectively). Similarly, a global longitudinal strain > –14.5% was able to predict an SF-36 score < 70 at six months post-discharge (AUC = 0.98 [95% CI: 0.90–1.00; p = 0.023]). Conclusion: A lymphocyte count ≤ 971 cells/mm³ showed good accuracy in predicting the need for invasive mechanical ventilation among hospitalized COVID-19 survivors. Additionally, there was significant recovery in cardiorespiratory function, exercise tolerance, and quality of life within six months after hospital discharge in this patient population.
Investigation of cardiorespiratory predictors in hospitalized COVID-19 survivors followed for 6 months after hospital discharge
Keywords: SARS-CoV-2; Marcadores prognósticos; Acompanhamento; Linfopenia; COVID-19; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE